A new species of Paspalum (Poaceae, Paniceae) from central Brazil - Oliveira, Regina C. (2005)
Paspalum vallsii, a new species in Paspalum sect. Pectinata from cerrado areas of central Brazil, is described and illustrated. It is most similar to P. reticulinerve, from which it differs by having solitary, longer spikelets with the upper glume and the lower lemma glabrous. It differs also from P. imbricatum and P. aspidiotes by having a narrower rachis. A key to the species of Paspalum sect. Pectinata is provided.